Cortisol in saliva and plasma of cattle after ACTH administration and milking - Negrão, J. A.; Porcionato, M. A. [UNESP]; De Passillé, A. M.; Rushen, J. (American Dairy Science Association, 2004)
Interest in the measurement of salivary cortisol has increased recently because saliva can be easily collected before and after an imposed stress. This study evaluated the relationship between plasma and salivary concentrations of cortisol following ACTH administration in calves (experiment 1) and machine milking of adult cows (experiment 2). A catheter was inserted into the jugular vein of all animals 72 h before the beginning of experiments. Blood and saliva samples were collected before and after ACTH administration (0.6 IU/kg BW) in calves or before and after machine milking of cows. Using a cotton swab, each saliva sample was taken immediately following the blood sample. In general, cortisol profiles were similar in plasma and saliva and correlated in both experiments; however, plasma concentrations were significantly higher than salivary concentrations. In addition, the differences between cortisol concentrations measured in saliva and plasma within each experiment varied substantially between animals and samples. Furthermore, in experiment 2, nearly 10% of salivary samples were below limits of detection. The sharp peaks in cortisol after ACTH administration in both the plasma and saliva were reflected adrenal stimulation. In addition, increases in cortisol in response to milking in both the plasma and saliva suggest that salivary sampling is a reliable option when studying cortisol responses to normal physiological events.
Keywords: ACTH administration; Cortisol; Plasma; Saliva